General anesthesia with local infiltration reduces urine retention rate and prolongs analgesic effect than spinal anesthesia for hemorrhoidectomy - Lin, Chun-Yu; Liu, Yi-Chun; Chen, Jun-Peng; Hsu, Pei-Hsuan; Chang, Szu-Ling (Frontiers in Surgery, 2024)
Introduction Postoperative pain and complications pose significant challenges following a hemorrhoidectomy. Attaining effective anesthesia with minimal complications is crucial. The ideal anesthesia method for ambulatory hemorrhoidectomy remains uncertain. This study aimed to investigate whether the combination of general anesthesia plus local infiltration (GAL) is associated with lower complications and reduced pain compared to spinal anesthesia (SA) in the context of hemorrhoidectomy. Methods This retrospective single-center cohort study, conducted in a tertiary medical center in East Asia, evaluated excisional hemorrhoidectomies performed between January 1, 2017, and March 31, 2023, utilizing GAL or SA. Data on the six most common complications-pain, constipation, acute urine retention (AUR), bleeding, nausea, and headache-were extracted from medical records. A total of 550 hemorrhoidectomies were included: 220 in the GAL group and 330 in the SA group. Patient characteristics were comparable between the two groups. Results The AUR rate was significantly lower in the GAL group compared to the SA group (15.5% vs. 32.1%, P < 0.001). Although the proportion of pain scores ≥4 did not differ significantly between the GAL and SA groups (36.2% vs. 39.8%, P = 0.429), the pain score curve indicated a stable trend. Overall, the GAL group exhibited a lower rate of adverse effects (56.9% vs. 67.4%, P = 0.023). There were no significant differences in the rates of other complications and emergency department readmission between the GAL and SA groups. Discussion GAL emerges as a favorable choice for anesthesia in hemorrhoidectomy, demonstrating a lower incidence of urine retention and a prolonged analgesic effect in multiple hemorrhoidectomies. These findings support the conclusion that GAL represents an optimal anesthetic method for enhancing the postoperative experience in patients undergoing hemorrhoidectomy.